A physical model of sprinting - Gaudet, S. (Journal of Biomechanics, 2014)
A new physical model of all-out sprinting is presented. The first models for the applied forces in the block, drive and maintenance phases, as well as for braking forces, are proposed and are based on experimental observations. The applied forces and the aerodynamic drag forces along with the speed and position of the sprinter are calculated by the model as functions of time. The model's unknown parameters are physically relevant and are quantitatively comparable to quantities measured experimentally. A novel mathematical method, not based on curve fitting, is proposed along with the model which requires two observable quantities, time of first step and start of maintenance phase, and four time splits. The model was validated by modeling several elite sprints from available split data, as well as measured splits for non-elite sprinters, over 100 m and 200 m distances. Excellent agreement between the split times and the simulated times was obtained and the model was shown to accurately predict 100 m times from 60 m splits for non-elite runners and 200 m times from 100 m splits for elite sprinters. The model was also applied to the study of wind and altitude effects for elite sprinters in 100 and 200 m sprints. The model presented in this paper may also be useful as a coaching tool for non-elite sprinters by enabling comparisons with elite sprinters, the identification of weaknesses (comparing phases, braking coefficient) and by allowing predictions of 100 m times based on 60 m (indoor) performances and 200 m times based on 100 m splits.